Urban labour in informal sector : a case study of Visakhapatnam City - Sreeramamurty, Kudamala (Delhi : B.R. Pub. Corp. ; New Delhi, India : Distributed by D.K. Publishers' Distributors, 1986)
Study of a city in Andhra Pradesh.
Includes index.
Bibliography: p. [128]-137.
Keywords: Labor supply -- India -- Vishakhapatnam -- Case studies; Labor mobility -- India -- Vishakhapatnam -- Case studies; Labor supply -- India -- Case studies; Labor mobility -- India -- Case studies